Ricuh Skandal Laporan Keuangan : Bagaimana Menilai Kinerja Keuangan PT. Garuda Indonesia,Tbk Menggunanakan Analisis Du Pont? - Yuniar Fitriyani (Jurnal Ecogen, 2023)
PT Garuda Indonesia, Tbk is the government's largest airline company, experienced irregularities in its 2018 financial statements which were published stating a profit, while the previous quarter's financial statements reported a loss. This irregularity reaped a polemic which ended with a sanction from the OJK in the form of a fine and the need to restate financial statements. The purpose of this study is to determine the financial performance of PT Garuda Indonesia, Tbk after the restatement using the Du Pont System analysis so that the causes of the ups and downs of the ROE, ROI, NPM and TATO variables as components of the analysis are known, so that the company can prepare the type of strategy taken to avoid severity. The results of the study found that the financial performance of PT Garuda Indonesia Tbk is in an unhealthy condition.